Granting Clemency To Narcotics Convicts: Overview From The Political Perspective Of Indonesian Criminal Law - Puluhulawa, Irlan (JURNAL LEGALITAS, 2021)
This research aims to examine the granting of clemency by the president to convicts of narcotics cases in the perspective of legal politics. In Law No. 22 of 2002 concerning Clemency, it does not specifically explain the category of crimes that can or cannot be granted clemency. Also, the Clemency Law does not specify the reasons that can be used by the applicant. There are two main problems in this study, namely (1) What is the mechanism for granting clemency to narcotics convicts? and (2) How is the legal politics of granting clemency by the president to convicts of narcotics cases in the future? This study uses a normative research method with a statutory approach, an analytical and legal conceptual approach, and a case approach. Based on this research, it can be concluded that the mechanism for granting clemency to narcotics convicts based on Law No. 22 of 2002 concerning clemency is the same as the mechanism for granting clemency in general or there is no special classification for certain crimes. Then the researcher recommends to revise the clemency law by adding the classification of extraordinary crimes in this case drugs as an exception from granting clemency. Then the consideration of the Supreme Court must take precedence in the clemency application process before appealing to the president.